Application of PV systems in the process of drying fish for traditional fisherman - I Gusti Made Ngurah Desnanjaya; I Komang Arya Ganda Wiguna; I Made Aditya Nugraha (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
The catch of fish is so large and often not completely sold, causing the fish to be wasted for free. This situation even indirectly causes environmental pollution around the area where fishermen live. To overcome this problem, a fish drying machine was made using a PV system. This tool is also a form of solving the problem of the traditional fish drying process which is sometimes not clean, safe, and depends on direct sunlight. This PV system can meet 169.95% of the need for 240 Wh/day of electrical energy from fish dryers. PV system can produce electrical energy for 407.81 Wh/day, where the largest energy can reach 520 Wh and the smallest is 160.8 Wh. The results of the analysis of the impact of using fish dryers socially and economically also gave significant results (p<0.005), where there was an increase from before and after the use of fish dryers experienced by fishermen. When viewed from the perspective of fishermen on the tool, the accuracy of the use of the tool, the benefit factor, and the shape of the fish dryer, the fishermen gave a good response, with an average value of 4.19-5.26.